Warming up the Climate Change Debate: A Challenge to Policy based on Adaptation - Nightingale, Andrea J (Journal of Forest and Livelihood, 2009)
With growing consensus on the fact of climate change, concerns of enhancing adaptive capacity are on the rise. Adaptation, as currently understood, is about whether farmers will have enough knowledge to farm differently. I suggest that the real concern is how it will shift social and geo?political systems and what that will mean for inequality, deliberative democracy and resource distribution. I argue that we need to take account of how social and ecological systems co?emerge, and understand adaptation as a contested, negotiated and power?laden process. Key words: climate change, adaptation, social capital, power, knowledge Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.84-89